THE AUTHORSHIP OF THE HISTORIA AUGUSTA: TWO NEW COMPUTATIONAL STUDIES. - STOVER, JUSTIN A.; KESTEMONT, MIKE (Bulletin of the Institute of Classical Studies, 2016)
The case of the Historia Augusta, a collection of imperial biographies from Hadrian to Carus supposedly written by six different authors, provided the impetus for the introduction of computational methods into the Echtheitskritik of ancient authors in 1979. After a flurry of studies in the 1990s, interest waned, particularly because most of those studies seemed to support conclusions incompatible with the scholarly consensus on the question. In the paper, we approach this question with the new tool of authorship verification - one of the most promising approaches in forensic stylometry today - as well as the established method of principal components analysis to demonstrate that there is no simple alternative between single and multiple authorship, and that the results of a computational analysis are in fact compatible with the results obtained from historical, literary, and philological analysis.